Makna Sentralisasi, Desentralisasi, Dekonsentrasi, dan Medebewin dalam Otonomi Daerah di Indonesia - Zaenal Arifin; Drajat Wahyu Sasongko (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
All this time latter, there is tendency that the interpretation of regional or local autonomy is used by the concerned authority to launch manpower of arrogance over his local power to against central government psychologically. Meanwhile he arises vested interest of the powerful authority where people would be sacrificed. So this problem must be expressed in mind by every official either in region or in central government because the existence of regional/local autonomy merely for people, not opportunity to disintegrate unitary state of Republic of Indonesia, but constitutes responsive reality of unifotmily and regional/local sources and resources which must be utilized in mazimum either for advancement or development regionally and actually in frame of unity of Indonesia.